2019
DOI: 10.3989/gya.1055182
|View full text |Cite
|
Sign up to set email alerts
|

Textural properties, sensory acceptance and fatty acid profile of cooked meat batters employing pumpkin seed paste or soybean oil oleogel as fat replacers

Abstract: Oleogel from soybean oil and pumpkin seed paste were proposed as full replacements for pork backfat to decrease the saturated fat contents and improve the PUFA/SFA ratio in meat batters. Textural compression, along with shear and penetration tests provided similar information related to meat batter structure according to the type of fat, showing that a tougher but brittle texture was produced. Meat batters with fat replacers were darker and less red, but more yellow due to the incorporation of vegetable oil. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…The author concluded that substitution of pork fat with soybean oil emulsion enhanced the product stability of sausages, but that replacing soybean protein isolate with fish protein isolate as the emulsifier could reinforce the protein matrix, decreasing the cooking loss and improving the texture profile with increasing fat substitution (25%, 35%, and 45%). In contrast, Ferrer-González et al (2019) showed that using soybean oil oleogels as a fat replacer maintained the same overall fat content (crude fat) and, thus, the caloric content of the control sample. However, the lipid profile improved because of the increased PUFA level from 2.77% to 6.61% and PUFA/SFA ratio from 0.62 to 2.42.…”
Section: Soybean Oilmentioning
confidence: 86%
See 3 more Smart Citations
“…The author concluded that substitution of pork fat with soybean oil emulsion enhanced the product stability of sausages, but that replacing soybean protein isolate with fish protein isolate as the emulsifier could reinforce the protein matrix, decreasing the cooking loss and improving the texture profile with increasing fat substitution (25%, 35%, and 45%). In contrast, Ferrer-González et al (2019) showed that using soybean oil oleogels as a fat replacer maintained the same overall fat content (crude fat) and, thus, the caloric content of the control sample. However, the lipid profile improved because of the increased PUFA level from 2.77% to 6.61% and PUFA/SFA ratio from 0.62 to 2.42.…”
Section: Soybean Oilmentioning
confidence: 86%
“…In contrast, Ferrer‐González et al. (2019) showed that using soybean oil oleogels as a fat replacer maintained the same overall fat content (crude fat) and, thus, the caloric content of the control sample. However, the lipid profile improved because of the increased PUFA level from 2.77% to 6.61% and PUFA/SFA ratio from 0.62 to 2.42.…”
Section: Modification Of Traditional Processed Meat Productsmentioning
confidence: 92%
See 2 more Smart Citations
“…Along this line researches claim that oleogel applications have satisfactory oxidative stability without the addition antioxidants (AOX). 49,51,52 To avoid a meaningless discussion on the level of POV that represents acceptable states of oxidation the effect of AOX addition was evaluated. For this purpose, vitamin E (0.01% (w/w)) was added to the 10%-oleogels with either SO (SO + E) or SFW (SFW + E) and to CO (CO + E) prior to production of the bouillon cube.…”
Section: Food and Functionmentioning
confidence: 99%